2001
DOI: 10.1086/323999
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Anovulation and Early Menopause among Women Enrolled in Selected Adult AIDS Clinical Trials Group Studies

Abstract: To obtain information on the prevalence of anovulation and early menopause and on pituitary-gonadal function among human immunodeficiency virus type 1-infected women, a study was undertaken that used stored serum samples from women aged 20-42 years who participated in selected Adult AIDS Clinical Trials Group protocols. Defined progesterone and follicle-stimulating hormone (FSH) levels were considered presumptive evidence of ovulation and of menopause, respectively. Anovulation occurred in 16 (48%) of 33 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
12

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 14 publications
(18 reference statements)
3
57
2
12
Order By: Relevance
“…Some authors have found no association with CD4 Count, HIV viral load and the use of ART, (12,14,19) whereas lower CD4 count has been shown to be a risk factor by others. (16)(17)(18) Evidence for a link between immunosuppression and menopause is further strengthened by data suggesting that lower CD4 count is associated with anovulatory cycles (22) and decreased levels of anti-mullerian hormone (AMH), a marker of ovarian reserve. (23) Furthermore, deranged follicle-stimulating hormone (FSH) levels have been described both in HIV infection itself and with use of ART, which may affect the diagnostic value of FSH in this group of women.…”
Section: Natural History Of the Menopause In Women Living With Hivmentioning
confidence: 99%
“…Some authors have found no association with CD4 Count, HIV viral load and the use of ART, (12,14,19) whereas lower CD4 count has been shown to be a risk factor by others. (16)(17)(18) Evidence for a link between immunosuppression and menopause is further strengthened by data suggesting that lower CD4 count is associated with anovulatory cycles (22) and decreased levels of anti-mullerian hormone (AMH), a marker of ovarian reserve. (23) Furthermore, deranged follicle-stimulating hormone (FSH) levels have been described both in HIV infection itself and with use of ART, which may affect the diagnostic value of FSH in this group of women.…”
Section: Natural History Of the Menopause In Women Living With Hivmentioning
confidence: 99%
“…Furthermore, long periods of amenorrhea that occur in these women may explain the estrogen depletion that often occurs. This depletion can affect bone health, because estrogen is a protective factor [13][14][15]. There are also other factors associated with bone loss, such as smoking, alcohol consumption, and low weight, which seem to be more frequent in HIVinfected women [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ovulatory function in HIVseropositive women have mixed results. While anovulatory cycles are reported to occur in 5-31% of healthy women with regular menses (27,28), they were reported in 48% of HIV-infected women in one small study, with a trend to occur more in women with low CD4 cell counts (29). Another small study reported anovulatory cycles in almost one third of HIV-positive women reporting normal menses (30), but a larger study of 55 HIV-infected and 10 negative controls reported ovulatory cycles in 96% of the seropositive and 78% of the seronegative women (31).…”
Section: Menstrual Disordersmentioning
confidence: 92%
“…One study suggests an increase in serum FSH levels in seropositive women when compared to controls (25), and a study of 24 HIV-positive women aged 20-42 years reported a serum FSH level consistent with menopause in 8% (29). Menopause may be difficult to ascertain in this population because of amenorrhea secondary to wasting, and confusion between climacteric symptoms and manifestations of coincident illness such as tuberculosis or side effects of drugs such as Efavirenz (10).…”
Section: Menstrual Disordersmentioning
confidence: 99%